(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Comprehensive sexuality education is seen as a key intervention to address the holistic development of adolescents with proper knowledge at the grassroots level. Lack of inclusion of the learners in the school curricular, discussions at community level, many a times imposes the superstitious practices those are restricting proper development. Breaking the Silence approach, is designed with a curriculum implementation was developed and tested in the district of Boudh. . This paper is a formative evaluation using case study method to capture the best practices. Comprehensive sexuality education (CSE) is being implemented with a greater commitment to practice as a result of global networks and initiatives. The expertise in guidance, designing curricula, and strengthening implementation tools and techniques is coming up with a wide range of approaches. The present study suggests a behavior change approach through sharing best practices in the Boudh district of Disha, India, for CSE implementation. This report provides an overview of the status of CSE implementation, drawing on specific information generated through analysis of the qualitative data collected from the field. The report examines the evidence base for CSE and, through a series of case studies, explores initiatives that are setting the standard and pioneering new practices in the delivery of CSE.